2018
DOI: 10.14715/cmb/2018.64.14.8
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against streptozotocin-induced diabetic cardiomyopathy by the phosphorylation of vascular endothelial growth factor-A (VEGF-A)

Abstract: The aim of the present study is to investigate if the melatonin has any protective effect on diabetic cardiomyopathy and antioxidant enzymes via phosphorylation of vascular endothelial growth factor-A (VEGF-A). A total of 40 male Wistar rats were enrolled in the study. Rats were divided into four groups: group 1 (control, n=10), group 2 (DM, n=10), group 3 (melatonin, n=10), and group 4 (melatonin+DM, n=10). Melatonin was injected intraperitoneally at a dose of 50 mg/kg/day for 56 days to group 3 and group 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Moreover, melatonin administration reduced insulin resistance and blood glucose level in high fat diet diabetic mice according to Sartori et al 17 . At night, individuals with type II diabetes release less melatonin than healthy individuals 18 . The studies of Heo et al 19 and Xu et al 20 showed that one dose of melatonin modified the glucose tolerance test in healthy pre-menopausal and post-menopausal females.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, melatonin administration reduced insulin resistance and blood glucose level in high fat diet diabetic mice according to Sartori et al 17 . At night, individuals with type II diabetes release less melatonin than healthy individuals 18 . The studies of Heo et al 19 and Xu et al 20 showed that one dose of melatonin modified the glucose tolerance test in healthy pre-menopausal and post-menopausal females.…”
Section: Introductionmentioning
confidence: 93%
“…Melatonin has been considered as a potential therapeutic agent for DCM because of its diverse beneficial actions. For example, melatonin can elicit an antioxidative stress action via decreasing mTOR level or increasing vascular endothelial growth factor‐A (VEGF‐A) phosphorylation in rats with DCM . Wang et al reported that melatonin can improve mitophagy activity via suppressing Mst1 in DCM .…”
Section: Discussionmentioning
confidence: 99%
“…For example, melatonin can elicit an antioxidative stress action via decreasing mTOR level or increasing vascular endothelial growth factor-A (VEGF-A) phosphorylation in rats with DCM. 36,37 Wang et al reported that melatonin can improve mitophagy activity via suppressing Mst1 in DCM. 38 Melatonin treatment alleviates cardiac function through inhibition of Syk-mitochondrial complex I-SERCA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Ctr group: pregnant rats received a basal diet and normal drinking water. Mel group: pregnant rats received a basal diet, normal drinking water and melatonin by oral gavage (50 mg/kg/day [ [26] , [27] , [28] ]; M5250, Sigma, MO, USA). FMT group: pregnant rats received a basal diet, normal drinking water and fecal suspension by oral gavage (0.005 ml/g/day [ 29 ]; see 2.3 FMT for production of fecal suspension).…”
Section: Methodsmentioning
confidence: 99%